Knowledge transfer to and within tourism : academic, industry and government bridges - Scott, Noel, 1958-; Van Niekerk, T., Mrs.; de Martino, Marcella (Emerald Publishing Limited, 2017)
There have been a number of sporadic and disconnected initiatives to improve knowledge transfer between the tourism academia, government and industry. This volume presents and analyses 17 examples of knowledge transfer from countries around the world to identify future directions for business and government managers and academic researchers. Many of the chapters were presented at the first t-Forum global conference. The chapters emphasise the value from academic leadership in developing cohesion and links amongst small business and government, and the importance of a shared innovative vision beyond individual private and public organization objectives. Successful initiatives rely on the personal characteristics of key stakeholders as well as institutional arrangements, emphasising action learning and challenging traditional academic research processes. Best practice knowledge transfer requires government, industry and academia in partnership engaged in open dialogue and debate for project success. Knowledge transfer provides an opportunity to address unprecedented societal, environmental and technological change and disruption.
Obsahuje index.
Keywords: Tourism.; elektronické knihy; electronic books